T2 Vitamin D supplementation reduces perioperative systemic and alveolar inflammation in patients undergoing oesophagectomy: Results of the Vindaloo Trial. (12th November 2015) - Dancer, RCA; Parekh, D; Scott, A; Perkins, GD; Thickett, DR
Abstract : Vitamin D deficiency is associated with increased risk of ARDS post-oesophagectomy. We recruited patients to a double-blind, randomised controlled trial of high dose Vitamin D supplementation 3–14 days pre-oesophagectomy. 79 patients were randomised to receive placebo or 300, 000 IU oral Vitamin D liquid 3–14 days prior to oesophagectomy. Blood samples were collected pre-dose, post-dose (pre-op) and post-op and analysed for 25-OH and 1, 25-dOH Vitamin D, inflammatory cells and cytokines. Broncho-alveolar lavage fluid was collected at the end of the operation. PICCO biomarkers of alveolar capillary damage (EVLWI and PVPI) were measured pre- and post-op. Pre-operative supplementation with Vitamin D was well tolerated with no SUSARs and significantly increased circulating 25-OH and 1, 25-OH Vitamin D (p < 0.0001). This was associated with reduced systemic inflammation (IL-6 (p = 0.02) and IL-8 (p = 0.002)) and an increase in circulatory Treg (p = 0.027). Changes in PICCO biomarkers were lower in supplemented patients suggesting lower perioperative alveolar oedema (EVLWI p = 0.05, PVPI p = 0.04). This did not result in a significant difference in oxygenation at 24 h. Post-op, systemic and alveolar alarmin (IL-1B, IL-6, IL-8) response was similar in treated and untreated patients but the systemic release of IL-1ra (p = 0.046), sTNFR-1 (p = 0.05) and s-TNFR-2 (p = 0.02) were elevated in treated patients. There was also evidence of decreased alveolar macrophage efferocytosis in patients with Vitamin D deficiency (p = 0.003). Clinical diagnoses of ARDS were significantly lower in this cohort than in previous cohorts, but the study was not powered to detect that outcome. Mortality post-operative was not significantly different at 30 or 90 days but there is a significant difference after 300 days of follow-up (placebo 33% mortality, Vitamin D 8% mortality p = 0.033). In conclusion, vitamin D supplementation was a safe, well tolerated pre-operative intervention that reduced systemic inflammation and biomarkers of alveolar oedema. With evidence of enhanced anti-inflammatory mechanism that may have influenced longer term post-operative survival, Vitamin D deficiency should be identified and treated in patients at risk of ARDS.